Indoor volatile organic compound (VOC) detection and air quality analysis - Bian, Ce (2015)
Many organizations has set standard on the level of Volatile Organic Compounds (VOCs) in indoor environment. They generally possess low boiling point thus easier for escape from the liquid or solid form and mix into the surrounding air. VOCs found in home, school, office and buildings are formaldehyde, alcohol, ozone and etc. Long-term exposure to VOCs will incur negative health impact on human. Gases like carbon dioxide also finds their own places in indoor environment. In the scope of this project, an air quality detection and analysis system is built. Alcohol and formaldehyde are chosen to be the target VOCs that are to be detected. And carbon monoxide is also chosen as a measure to assess the air quality. A microcontroller is used to set up a sensor system. The concentration of target substance in air are detected and converted to relevant units. These data is transmitted to and processed by the microcontroller, Arduino Uno Rev3 and Arduino WiFi Shield. Local web server is established to share the real-time air quality.